(untitled) (Journal of Scientific Research, 2025)
The Bianchi III anisotropic cosmological model has been examined within the context of f (T) gravity, where f (T) represents Teleparallel gravity. The Main objective is to investigate the instability of the universe by analyzing the derivative of the pressure function with respect to the matter density function. The accelerated expansion of the universe has been examined. The equation of state (EOS) is found to vary with time. To accomplish this derive exact solutions for the space-time field equations in an exponential form and consider a power-law approach with a non-dissipative anisotropic fluid distribution. By analyzing pressures in the spatial directions, obtained a set of energy condition equations, which are then used to formulate the Dark Energy equations.